Comparing Website Implementation Between Cloud Services and Conventional Hosting Methods - Jaganathan, Johnathan (IRC, 2020)
This dissertation report is written for the comparison of website implementation between cloud services and conventional hosting through the means of a case study of data centered web application for process safety information plant. In this digital age, a website is an essential tool for interaction, communication and visualization for businesses, organizations and individuals. Thus, new ideas and methods regarding the development and implementation of websites are continuously being churned out. One of the new developments in this field is cloud services. Therefore, decision makers and software developers have an alternative option in terms of website development and implementation besides the more conventional hosting method. This project has been conducted to compare both these methods and come up with a comparison for key individuals to go about choosing between cloud services and conventional hosting. To complete this project, two phases of methodology have been used, which are preliminary studies and prototype development. To conduct the preliminary studies, literature review of the project and surveys were completed. For the system development on the other hand, iterative methodology was done in two phases. These phases acted as guidelines to complete the work on developing the prototypes through cloud services and conventional methods. At the end of this project development, it is hoped that key decision makers and website developers will have a clear view and a comparison reference to refer when choosing between cloud services and conventional methods to develop and implement a website.